A Cross-over Pilot Study on the Effects of Classical Guitar Instruction on Motor and Non-Motor Symptoms in People with Parkinson’s Disease - Christopher Adams; Greg Fulton (Neuroscience Insights)
Background: A previous randomized pre-post cross-over study with 26 participants found positive changes in motor and non-motor symptoms in people with Parkinson’s disease (PwPD) after six weeks of group classical guitar sessions but not customary and usual treatment. Objective: To determine if a six-week group classical guitar instruction program improved motor function, mood, and quality of life for PwPD in comparison to a six-week group exercise program in a non-randomized cross-over pilot study. Methods: Eighteen PwPD were enrolled and 15 completed the study. Group 1 (N = 10) received a six-week group guitar instruction program, and then a six-week group exercise program. Group 2 (N = 8) received a six-week group exercise program, and then a six-week guitar instruction program. Assessments were at baseline, six weeks, and 12 weeks. The groups were combined for analysis by two-tailed paired t -tests due to the low sample size. Assessments included the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) motor sub-section, Hoehn and Yahr scale, Parkinson’s Disease Questionnaire-39 (PDQ-39), Apathy Evaluation Scale-Self (AES-S), and Beck Depression Inventory II (BDI-II). Results: MDS-UPDRS mean motor scores decreased compared to pre-test scores with group guitar instruction (−5.3 points, P  < .001), but not group exercise (−0.47 points, P  = .85). BDI-II mean scores decreased by 2.13 ( P  = .08) and 1.87 points ( P  = .02) with group guitar instruction and group exercise, respectively. PDQ-39 mean scores decreased by 1.93 ( P  = .02) and 2.52 ( P  = .02) points with group guitar instruction and group exercise, respectively. AES-S mean scores decreased with group exercise (−2.40 points, P  = .03) but not group guitar instruction (−2.4 points, P  = .26). Conclusions: Group guitar instruction could potentially help with both motor and non-motor symptoms in PwPD. There appears to be a specific effect of group guitar instruction on MDS-UPDRS motor scores that is not due to regular meetings and general exercises. This unfunded study was registered at ClinicalTrials.gov (NCT05917704).